Comparison of the Blood and Lymphatic Microvessel Density of Pleomorphic Adenoma and Basal Cell Adenoma - Andresa Borges Soares; Albina Alternarli; Thais Ribeiro De Oliveira; Felipe de Oliveira Fonseca Rodrigues; Alfredo Ribeiro-Silva; Danilo Figueiredo Soave; Fabricio Passador-Santos; Suellen Trentin Brum; Marcelo Henrique Napimoga; Vera Cavalcanti De Araújo (SAGE Publishing, 2015)
Background Pleomorphic adenoma (PA) is the most common tumor of the salivary gland, while basal cell adenoma (BCA) is an uncommon neoplasm. Blood and lymphatic vessels are crucial for tumor metabolism. The aim of this study was to compare the blood and lymphatic vascular density and vascular and endothelial growth factor (VEGF) expression in PA and BCA tumors. In addition, cell proliferation was evaluated in these tumors. Methods Blood and lymphatic vessel content, VEGF expression, and cell proliferation were analyzed in 30 cases of PA and 13 cases of BCA by immu-nohistochemistry using antibodies for CD34, CD105, D2-40, VEGF, and Mcm -2. Results Regarding CD34 and CD105 expression, PA demonstrated a high vascularity and a low number of positive vessels, respectively. D2-40-positive lymphatic vessels were mainly located in the tumor capsules, with small intratumoral lymphatic vessels observed occasionally. VEGF expression revealed a remarkably heterogeneous immunoreactivity, alternating from weak or negative to positive or intense. BCA presented significantly higher CD34, CD34, CD105, D2-40, and VEGF expression compared to PA. No significant difference was found in cell proliferation between the tumors. Conclusion Although PA and BCA are considered part of the same spectrum of differentiation, this study showed that the blood and lymphatic vascularization of these tumors is different.